Insights on wood combustion generated proinflammatory ultrafine particles (UFP). (15th January 2017) - Corsini, Emanuela; Ozgen, Senem; Papale, Angela; Galbiati, Valentina; Lonati, Giovanni; Fermo, Paola; Corbella, Lorenza; Valli, Gianluigi; Bernardoni, Vera; Dell'Acqua, Manuela; Becagli, Silvia; Caruso, Donatella; et al.
Highlights: Wood stoves generate UFP more biologically active compared to pellet stoves. Different wood essences generate UFP with different composition and biological activity. Different cell types respond differently to UFP. Abstract: This study aimed to collect, characterize ultrafine particles (UFP) generated from the combustion of wood pellets and logs (softwood and hardwood) and to evaluate their pro-inflammatory effects in THP-1 and A549 cells. Both cell lines responded to UFP producing interleukin-8 (IL-8), with wood log UFP being more active compared to pellet UFP. With the exception of higher effect observed with beech wood log UFP in THP-1, the ability of soft or hard woods to induce IL-8 release was similar. In addition, on weight mass, IL-8 release was similar or lower compared to diesel exhaust particles (DEP), arguing against higher biological activity of smaller size particles. UFP-induced IL-8 could be reduced by SB203580, indicating a role of p38MAPK activation in IL-8 production. The higher activity of beech wood log UFP in THP-1 was not due to higher uptake or endotoxin contamination. Qualitatively different protein adsorption profiles were observed, with less proteins bound to beech UFP compared to conifer UFP or DEP, which may provide higher intracellular availability of bioactive components, i.e. levoglucosan and galactosan, toward which THP-1 were more responsive compared to A549 cells. These results contribute to our understanding of particles emitted by domestic appliances and their biological effects.